Advokasi Kebijakan Zero Overloading Angkutan Barang di Kabupaten Lamandau - Helani Asie; Ida Hayu Dwimawanti; Retno Sunu Astuti; Teuku Afrizal (Universitas Medan Area, 2022)
Road Traffic and Transportation as part of the national transportation system must develop its potential and role to realize security, safety, order and smooth traffic in order to support economic development and regional development. Road users in general, still do not fully comply with the regulations that have been set. However, the purpose of this regulation is to prevent unwanted things from happening. The enactment of Law Number 22 of 2009 concerning Road Traffic and Transportation replacing the old Law Number 14 of 1992, has brought about important changes in the way of life of road traffic in Indonesia. With the formulation of the problem, how is the role of the Lamandau Regency Transportation Service as a Stakeholder and how to implement zero overloading of freight transport in Lamandau Regency. This study was conducted to analyze the role of the Lamandau Regency Transportation Service as a stakeholder and presumably to describe zero overloading of freight transport in Lamandau Regency. The descriptive qualitative research method used in this study was intended to obtain information about zero overloading of freight transport in Lamandau Regency.